Biochemical and morphological perturbations in rat erythrocytes exposed to ethion: protective effect of vitamin E - Bhatti, G. K.; Bhatti, J. S.; Kiran, R.; Sandhir, R. (Cellular and Molecular Biology, 2011)
Erythrocyte membranes are an excellent model system to study interaction of pro-oxidants with membranes. The aim of the present study is to examine the effect of vitamin E on ethion-induced biochemical and morphological alterations in erythrocytes. Ethion was administered to the rats orally at a daily dose of 2.7 mg/kg body weight for a period of 7, 14, 21 and 28 days. The results from the present study show that administration of ethion resulted in oxidative damage to erythrocyte membranes as evident by increased lipid peroxidation and decreased phospholipid content. This was accompanied by decrease in membrane cholesterol levels. In addition, ethion exposure inhibited the activities of membrane bound enzymes; Na+ K+ ATPase and Mg2+ATPase. Scanning electron micrographs of erythrocytes from animals exposed to ethion revealed morphological changes. Supplementation of vitamin E (50 mg/kg body weight) to ethion exposed animals ameliorated the ethion-induced oxidative stress, restored membrane lipid composition and activity of membrane bound enzymes along with erythrocyte shape. The results clearly demonstrate that ethion-induced damage involves increase in oxidative stress that results in alterations in erythrocyte membrane structure and function. Furthermore, supplementation with vitamin E reversed ethion induced alterations suggesting its beneficial role in individuals exposed to ethion.